2008
DOI: 10.1111/j.1469-1795.2008.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in abundance of large herbivore populations: insights into the influence of dry season rainfall and elephant numbers from long‐term data

Abstract: International audienceIn some African protected areas, elephant populations have reached high densities causing concern about their influence on other forms of biodiversity, and in particular, other large herbivores. This has led to a debate whether management of elephant populations might need to be implemented. Surprisingly, few studies have focused on the influence of elephants on other herbivores and the existing results are conflicting. We investigated such influence in Hwange National Park, Zimbabwe, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 42 publications
2
37
0
Order By: Relevance
“…) and where most of the other herbivore species have shown declines in their populations (Valeix et al . ) rising concerns about the impact of elephants on other herbivore species. Our work shows that while there seem to be some costs associated to cryptic interference competition with elephants, these costs are not high enough to prevent other herbivores from accessing high‐quality resources at the peak of the dry season when water requirements are crucial.…”
Section: Discussionmentioning
confidence: 99%
“…) and where most of the other herbivore species have shown declines in their populations (Valeix et al . ) rising concerns about the impact of elephants on other herbivore species. Our work shows that while there seem to be some costs associated to cryptic interference competition with elephants, these costs are not high enough to prevent other herbivores from accessing high‐quality resources at the peak of the dry season when water requirements are crucial.…”
Section: Discussionmentioning
confidence: 99%
“…According to Fritz et al (2002) and Valeix et al (2008), elephants may compete with mesomixed feeders (such as impala), depending on the abundance and quality of the forage. However, Sinclair et al (2003) showed that predation is a factor defining herbivore densities on African savannas, particularly for small herbivores (<150 kg).…”
Section: Discussionmentioning
confidence: 99%
“…Fritz et al (2002) concluded that elephants compete with the smaller mesobrowser species for browse resources, as the relative contribution of these species declined with increasing elephant densities. Valeix et al (2008) also reported a possible negative influence of elephants on other herbivore species. Elephant impact, especially on the larger trees, could also have negative consequences for large browsing species such as giraffe (Fritz et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies try to demonstrate that populations of animals-from herbivores to top predators, verte brates and invertebrates-are limited by their food, and that the availability of this food is correlated with the weather (Ottichilo et al, 2001;Ogutu et al, 2003;Dunham et al, 2004;White, 2008;Valeix et al, 2008). Estes et al (2006) point out that research in this area is urgently needed to increase understanding of savana complex ecosystems.…”
Section: Introductionmentioning
confidence: 99%